RANCANG BANGUN POROS PADA MESIN PEMOTONG TULANG - Maulana, Aditya Rizky; Saleh, Agus (Jurnal TEDC; Vol 19 No 2 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i2.1130, 2025)
Along with population growth, diverse preferences and lifestyles, fluctuating prices, and increasing consumer financial capabilities, the need for animal protein-based foods such as meat has also increased. Increasing public awareness of the importance of balanced nutrition, population growth, and increasing financial capabilities of the community are factors that cause an increase in the desire to consume beef. Given the increasing need for meat and bones with relatively high community needs, special equipment is needed, namely a bone cutting machine, to help cut bones quickly. To make this machine, data was collected through observation and literature studies. The author used Solidwork 2020 to make the shaft of this bone cutting machine, then performed calculations manually. Based on the results of the shaft design, the torsional moment on the drive shaft was calculated as 13045 kg, the permissible shear stress was 4.1 kg/mm 2 , the main shaft diameter was 24 mm, the shear stress was 4.81 kg/mm 2 , the shaft length was 260 mm, and the torsional deflection was 0.72°. The results of the functional test of the bone cutting machine shaft can run according to plan. The results can be used as a teaching tool for mechanical engineering students, and the design of the cutting knife can be improved so that it can be used optimally and benefit society.